The stable isotope setting of Australopithecus sediba at Malapa, South Africa - Holt, Emily; Dirks, Paul; Placzek, Christa; Berger, Lee (South African Journal of Science, 2016)
We report δ13C and δ18O results from carbonate-cemented cave sediments at Malapa in South Africa. The sediments were deposited during a short-period magnetic reversal at 1.977±0.003 Ma, immediately preceding deposition of Facies D sediments that contain the type fossils of Australopithecus sediba. Values of δ13C range between -5.65 and -2.09 with an average of -4.58±0.54‰ (Vienna Pee Dee Belemnite, VPDB) and values of δ18O range between -6.14 and -3.84 with an average of -4.93±0.44‰ (VPDB). Despite signs of diagenetic alteration from metastable aragonite to calcite, the Malapa isotope values are similar to those obtained in two previous studies in South Africa for the same relative time period. Broadly, the Malapa δ13C values provide constraints on the palaeovegetation at Malapa. Because of the complex nature of the carbonate cements and mixed mineralogy in the samples, our estimates of vegetation type (C4-dominant) must be regarded as preliminary only. However, the indication of a mainly C4 landscape is in contrast to the reported diet of A. sediba, and suggests a diverse environment involving both grassland and riparian woodland.